Enhanced production of parthenocarpic cucumbers pollinated with stingless bees and Africanized honey bees in greenhouses - Nicodemo, Daniel [UNESP]; Malheiros, Euclides Braga [UNESP]; De Jong, David; Nogueira Couto, Regina Helena [UNESP] (Universidade Estadual de Londrina (UEL), 2013)
Crops have different levels of dependence on pollinators; this holds true even for cultivars of the same species, as in the case of cucumber (Cucumis sativus). The aim of this research was to assess the attractiveness of flowers of three Japanese parthenocarpic cucumber cultivars and evaluate the importance of Africanized bees (Apis mellifera), and the Brazilian native stingless bees, Jata (Tetragonisca angustula) and Ira (Nannotrigona testaceicornis) on fruit production. Several parameters, including frequency of bee visits to flowers as well as duration of nectar collection and fruit set were examined; additionally, fruit weight, length and diameter were evaluated. Three greenhouses located in Ribeirao Preto, SP, were used for planting three cucumber cultivars (Hokushin, Yoshinari and Soudai). The female flowers were more attractive than male flowers; however, Jata bees were not observed visiting the flowers. The Africanized and the Ira bees collected only nectar, with a visitation peak between 10 and 12h. Visits to female flowers had a longer duration than visits to male flower visits in all three cultivars. Africanized bee colonies declined due to loss of bees while in the greenhouse; the native stingless bee colonies did not suffer these losses. When bees were excluded, fruit set was 78%; however, when bees had access to the flowers, fruit set was significantly (19.2%) higher. Fruit size and weight did not differ with and without bees. This demonstrates that even in parthenocarpic cucumber cultivars, which do not require pollination in order to from fruits, fruit production is significantly increased by bee pollination.
Keywords: Apis mellifera; Nannotrigona testaceicornis; Tetragonisca angustula; Fruit set; parthenocarpic cucumber